The influence of promotion, service quality, and pricing on purchase decisions at Assalaam hypermarket - Hadi, Alfiansyah; Cahyani, Rusnandari Retno; Mutiasari, Annisa Indah (Junal Ilmu Manajemen, 2024)
This study aims to determine the effect of promotion, service quality, and price on purchasing decisions at Assalaam Hypermarket. This research is descriptive with a quantitative approach. The population consists of consumers shopping at Assalaam Hypermarket, with a sample of 150 respondents selected using non-random sampling techniques. The results indicate that promotion, service quality, and price significantly affect purchasing decisions. The calculation results obtained from the F-value (20.695) exceed the F-table (2.67), with a significant value of 0.000 < 0.05. Among the three variables, service quality has the most dominant influence on purchasing decisions.